Peran Mahkamah Konstitusi dalam Penegakan Hukum dan Mempertahankan Keseimbangan Kekuasaan dalam Sistem Pemerintahan Indonesia - Hasibuan, Selamat Sentosa; Rizki, Nurul; Siregar, Ivanda Yusuf (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to evaluate the role of the Constitutional Court (MK) in maintaining constitutional supremacy, democracy and balance of power in the Indonesian constitutional system. This research uses a qualitative approach with descriptive methods. Data was collected from primary sources in the form of statutory regulations, such as the 1945 Constitution of the Republic of Indonesia and Law Number 24 of 2003 concerning the Constitutional Court, as well as secondary sources in the form of books, legal journals and legal scientific articles. The research results show that the Constitutional Court has an important role in maintaining legal stability, maintaining the balance of power between state institutions, and upholding democratic principles and constitutional supremacy in Indonesia. Through its authority to carry out judicial reviews of laws and government policies, the Constitutional Court functions as the front guard in enforcing the law and maintaining the balance of power between the executive, legislative and judiciary. However, the role of the Constitutional Court often sparks debate regarding the limits of judicial intervention in public policy, showing the complexity in maintaining the balance of power. Therefore, this research contributes to understanding the role and challenges faced by the Constitutional Court in the context of the Indonesian constitutional system.